PERTANGGUNGJAWABAN KORPORASI MENURUT UNDANG-UNDANG NOMOR 1 TAHUN 2023 TENTANG KITAB UNDANG-UNDANG HUKUM PIDANA - Melissa, Aldisa; Rini Utami, Anta; Chatias Pratama, Riza (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
The criminal law formulation policy in Law Number 1 of 2023 concerning the Criminal Code brings the new rules up in enforcing criminal law in Indonesia. One of the changes towards these regulations includes determining corporations as the subject of criminal acts. This regulation was appeared since the law enforcers have been limited in imposing sanctions on corporations that violate statutory provisions all this time. Before the ratified of the Criminal Code, there were several laws besides the Criminal Code that previously determined the definition of a corporation and its forms of responsibility, such as the Law on the Eradication of Money Laundering, the Law on the Eradication of Corruption, Narcotics Law and other laws that regulate corporate responsibility. By designating corporations as subjects of criminal acts, it will make it easier for law enforcers to carry out investigations, inquiries and prosecutions.Keywords: Criminal Law Formulation, Corporate Responsibility, Subject of Criminal Acts.